An inertial S-iteration process - Aniruth Phon-on; Nifatamah Makaje; Areeyuth Sama-Ae; Kittiya Khongraphan (Fixed Point Theory and Applications, 2019)
Abstract In this paper, we establish a new iteration method, called an InerSP (an inertial S-iteration process), by combining a modified S-iteration process with the inertial extrapolation. This strategy is for speeding up the convergence of the algorithm. We then prove the convergence theorems of a sequence generated by our new method for finding a common fixed point of nonexpansive mappings in a Banach space. We also present numerical examples to illustrate that the acceleration of our algorithm is effective.